Consumer market segmentation in the Federal District according their environmental performance - Almeida, Alexandre Nascimento de; Santana, Elivaldo Ribeiro de; Gonçalves, Andréa de Oliveira; Angelo, Humberto (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
The objective of this work is to segment the consumer of the Distrito Federal - DF according to their environmental behavior. To this, from a random sample of 131 questionnaires, was applied the method of factor analysis to define the dimensions representing the environmental behavior of residents in the DF. The analysis revealed the existence of four dimensions, dividing consumers of the DF in the segments: 1) "Concerned by the pollution of garbage"; 2) "Highly aware to the environmental issue"; 3) " Concerned with the financial impact of the resource waste"; 4) "Unconcerned with the environment". Except for the "unconcerned with the environment," strategies of the environmental and social marketing can be effective, since they consider the different needs of specified groups. While the "concerned by the pollution of garbage" valorize the social recognition of their actions the "concerned with the financial impact of the resource waste" prioritize direct and indirect economic benefits. For the "highly aware to the environmental issue" the most important is to demonstrate the effectiveness of green actions, regardless of these will promote social recognition or promote economic advantage for the segment.